2010
DOI: 10.1016/j.jcp.2010.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Error estimation and anisotropic mesh refinement for 3d laminar aerodynamic flow simulations

Abstract: a b s t r a c tThis article considers a posteriori error estimation and anisotropic mesh refinement for three-dimensional laminar aerodynamic flow simulations. The optimal order symmetric interior penalty discontinuous Galerkin discretization which has previously been developed for the compressible Navier-Stokes equations in two dimensions is extended to three dimensions. Symmetry boundary conditions are given which allow to discretize and compute symmetric flows on the half model resulting in exactly the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 28 publications
2
73
0
Order By: Relevance
“…On each element of the patch, the gradient of the numerical solution has the highest accuracy at the super-convergent points, thus the high-order accurate expression of the reconstructed gradient on the patch is obtained by a least square fitting of the polynomial expressions (20) to the values of the gradient at the super-convergent points of the patch. Assuming that N s i super-convergent points, x i, , = 1 .…”
Section: Super-convergent Patch Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…On each element of the patch, the gradient of the numerical solution has the highest accuracy at the super-convergent points, thus the high-order accurate expression of the reconstructed gradient on the patch is obtained by a least square fitting of the polynomial expressions (20) to the values of the gradient at the super-convergent points of the patch. Assuming that N s i super-convergent points, x i, , = 1 .…”
Section: Super-convergent Patch Recoverymentioning
confidence: 99%
“…24 are reported the drag and lift coefficients computed with linear and quadratic elements, on three uniformly refined grids. For comparison, are reported also the reference values computed in [20] by extrapolating the results obtained with a higher order DG method. Observing the convergence of the drag coefficient in term of DOFs, it can be noted that there is no significant gain in using a higher order approximation, with respect to the second order.…”
Section: Laminar Flow Around a Delta Wingmentioning
confidence: 99%
“…Over the years, to overcome this contradiction and acquire optimum precision for the solution, several adaptive approaches have evolved (Harutyunyan, Izsák, van der Vegt, & Botchev, 2008;Hicken, 2012;Lee & Zhou, 2004;Leicht & Hartmann, 2010;Zhu & Zienkiewicz, 1997). The two fundamental concerns involved in the methods of mesh refinement are "error estimation" and "mesh density control through suitable scheme".…”
Section: Error Estimationsmentioning
confidence: 99%
“…If there is a boundary condition against one of the faces of the element, then that side is neglected in (23).…”
Section: 4mentioning
confidence: 99%
“…Zhu et al [45] compared a few of them and found that KXRCF provided very good results for typical one-dimensional shock problems. In addition, Leicht and Hartmann [23] used the jump between elements to determine the direction for anisotropic refinement. In this study we propose a new estimator which results from a combination of some of these detectors and has better efficiency.…”
Section: Introductionmentioning
confidence: 99%